2019
DOI: 10.1111/geb.12917
|View full text |Cite
|
Sign up to set email alerts
|

The spatial scale dependence of diazotrophic and bacterial community assembly in paddy soil

Abstract: Aim The factors driving microbial community β‐diversity (variation in composition) at different spatial scales yield fundamental insights into the mechanisms that maintain ecosystem biodiversity, which as yet are uncertain. Here, we explore whether spatial scale‐dependent patterns of β‐diversity vary between microbial functional groups and bacterial taxa (i.e., diazotrophic and bacterial communities) across local to regional scales (from metres to hundreds of kilometres). Location Eastern China. Time period Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 76 publications
5
44
1
Order By: Relevance
“…Alphaproteobacteria was the most abundant class found in forest soils, as has already been observed in other terrestrial ecosystems (Collavino et al, 2014; Gao et al, 2019). A previous study found that Cyanobacteria (10%) was the second most frequent N‐fixer in global soils (Gaby & Buckley, 2011).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Alphaproteobacteria was the most abundant class found in forest soils, as has already been observed in other terrestrial ecosystems (Collavino et al, 2014; Gao et al, 2019). A previous study found that Cyanobacteria (10%) was the second most frequent N‐fixer in global soils (Gaby & Buckley, 2011).…”
Section: Discussionsupporting
confidence: 69%
“…For example, Feng et al (2018) reported that soil pH played a major role in diazotrophic diversity and structure in farmlands. Gao et al (2019) found that soil pH was the most important abiotic factor that contributed to the variation of diazotrophic community β‐diversity in paddy soils at local and regional scales, followed by soil ammonium content and dissolved organic carbon. Shay et al (2015) observed that shifts in diazotrophic communities were best explained by pH in Douglas‐fir forests.…”
Section: Discussionmentioning
confidence: 99%
“…The paddy soil network had a greater modularity and included more mutual exclusion relationships compared with the non-paddy soil network. Continuous ploughing and waterlogged conditions could make this soil habitat more homogeneous, leading to relatively weak niche differentiation [13,32].…”
Section: Discussionmentioning
confidence: 99%
“…The continental and global biogeography of soil microbes has been investigated previously [5][6][7][8][9][10], providing a wealth of data regarding the association between microbial community dynamics and their habitat preferences [5,7], landscape ecological functions and services [6], and biogeochemistry and plant traits [9,11]. Most of these studies mapped microbial biogeography across natural ecosystems, but the impact of human interference as challenges to the well-established biogeographic patterns in naturaloccurring settings remains understudied [12][13][14]. There also has been con icting data associated with whether the microbial communities assemble through deterministic or stochastic processes [15,16], which can be better informed through a broad scale investigation across multiple eld sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the large spatial heterogeneity of plant density (42-2,221 stem/m 2 ), plant species richness (3-12 species/m 2 ), and soil moisture (4.03%-16.16%) may conceal the effects of restoration methods on the diversity of fungi and bacteria; thus more replications are needed to decrease the influence of site heterogeneity in the future. Moreover, the driver of the observed heterogeneity in fungal and bacterial diversity may change along time scales(Gao et al, 2019), especially in farmland, thus longterm experiments are needed to evaluate the effects of different restoration methods on the diversity of fungi and bacteria in the soil.…”
mentioning
confidence: 99%